Productivity of Bottom gillnet fishing gear on fish landing results at Fish Landing Base (PPI) Ujong Seurangga - Rizki Purnama Nanda; Miswar Edy; Fitriani Riska; Maulinda Maulinda (BIO Web of Conferences)
The bottom gillnet is a passive fishing gear resembling a rectangle, designed with floats on the top and sinkers on the bottom. Evaluating the productivity of the bottom gillnets is crucial for assessing their effectiveness in catching fish. This study examines the productivity of bottom gillnets using two mesh sizes: 1 3/4-inch and 2-inch. Conducted in 2 months in 2024 at the Fish Landing Base (PPI) Ujong Seurangga, the research employed survey and interviews methods with purposive sampling. Data analysis included calculation of production value per trip and per unit length of the net. The findings reveal that bottom gillnets with a 1 3/4-inch mesh size achieved a productivity of 1,870 kg/trip, while those with a 2-inch mesh size recorded 3,975 kg/trip. Productivity per sheet of net was 0.1 kg/sheet for the 1 3/4-inch mesh size and 0,2 kg/sheet for the 2-inch mesh size. A total of 33 fish species were identified during the study. The 1 3/4-inch mesh size caught 30 species (436 fish, 27,878 kg), while the 2- inch mesh caught 24 species (393 fish, 58,944 kg). These results highlight the efficiency and selectivity of different mesh size for bottom gillnet fishing.